Smoke and iron - Caine, Rachel (Caine, Rachel. Great Library, 2018)
"To save the Great Library, the unforgettable characters from Ink and Bone, Paper and Fire, and Ash and Quill put themselves in danger in the next thrilling adventure in the New York Times bestselling series. The opening moves of a deadly game have begun. Jess Brightwell has put himself in direct peril, with only his wits and skill to aid him in a game of cat and mouse with the Archivist Magister of the Great Library. With the world catching fire, and words printed on paper the spark that lights rebellion, it falls to smugglers, thieves, and scholars to save a library thousands of years in the making ... if they can stay alive long enough to outwit their enemies"--